2016
DOI: 10.14348/molcells.2016.2341
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of Peroxiredoxins in Inflammation

Abstract: Inflammation is a pathophysiological response to infection or tissue damage during which high levels of reactive oxygen and nitrogen species are produced by phagocytes to kill microorganisms. Reactive oxygen and nitrogen species serve also in the complex regulation of inflammatory processes. Recently, it has been proposed that peroxiredoxins may play key roles in innate immunity and inflammation. Indeed, peroxiredoxins are evolutionarily conserved peroxidases able to reduce, with high rate constants, hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 66 publications
(93 reference statements)
0
56
0
Order By: Relevance
“…In contrast, when the concentration of H 2 O 2 or ONOO − surpasses their signaling threshold, they promote oxidation of biomolecules, such as proteins, lipids, and particularly, nucleic acids [1, 3]. High levels of ROS released under control in phagocytes provide protection from invading bacteria and viruses [4]; however, uncontrolled and high levels of ROS breakdown cellular components leading to cancer, neurological disorders, and cardiovascular disease, to name a few [57]. Oxidation of the genome represents a critical location in which oxidatively-derived damage under high levels of ROS can lead to these diseases.…”
Section: Introduction1mentioning
confidence: 99%
“…In contrast, when the concentration of H 2 O 2 or ONOO − surpasses their signaling threshold, they promote oxidation of biomolecules, such as proteins, lipids, and particularly, nucleic acids [1, 3]. High levels of ROS released under control in phagocytes provide protection from invading bacteria and viruses [4]; however, uncontrolled and high levels of ROS breakdown cellular components leading to cancer, neurological disorders, and cardiovascular disease, to name a few [57]. Oxidation of the genome represents a critical location in which oxidatively-derived damage under high levels of ROS can lead to these diseases.…”
Section: Introduction1mentioning
confidence: 99%
“…Expression of Prx6 in various tissues has been shown to rise in marine animal models following bacterial stimuli (22,23). The same effect has been seen in mouse bone marrow-derived macrophages following stimulation with interferon gamma and lipopolysaccharide (24). One study demonstrated translocation of Prx6 to the plasma membrane during neutrophil activation and that this is required for optimal function of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (25).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, PRDX4 has a role in regulating the activation of NF-ĸB transcription factor and TNF-related apoptosis-inducing ligand (TRAIL) [56]. TRAIL is a transmembrane protein involved in apoptosis extrinsic pathway by binding to receptors DR4 or DR5.…”
Section: Peroxiredoxin-4 41 Peroxiredoxin-4 and Its Functionmentioning
confidence: 99%